The Role of Participative Learning on Post-Training Development - Fauzi, Ikka Kartika Abbas (International Journal of Psychosocial Rehabilitation, 2020)
Post-training development often finds less attention because the participant who has been finished training is usually presumed to be able and ready to apply the training outcomes. The amount of 74,2% early childhood educators which was involved as subject research at Kabupaten Sumedang and Kota Bandung is capable of applying only 5 to 10% of the training outcomes. Post-training development which should be conducted by Head school, as well as Early Childhood Education (ECE) overseers, is not sufficiently established. If it is conducted anyway, it rarely touches the needs of the ECE teacher. To solve this problem, Community based Participative learning is used as a model to carry out Post-Training Development. The result of the research is measured by using teacher performance assessment. There is 85,86% ECE teacher that are categorized as “good” and “very good”. Around 24,15% are categorized as “adequate” and “less.” The result of the research shows that Participative Learning can improve participants’ knowledge and skills in applying training outcomes because it serves as a medium for participant's peer-learning, consultancy media, self-development, and unifying instrument.